Investigating historical attribution: luminescence dating of bricks from a submerged structure in southeastern India - Morthekai, Paulramasamy; Singhal, Malika; Sharma, Suchinder K.; Sivasubramaniam, Sudhakar; Kamarasu, Muthalankurichi; Singh, Priyanka; Chauhan, Naveen; Kumar, Kamlesh; Nawaz, Sheikh Ali; Khonde, Nitesh (Frontiers in Environmental Archaeology, 2025)
By 2019, a long brick platform with some structures was exposed when the Thamirabarani River, the southernmost river in the city of Thirunelveli, dried up. The civic society rejoiced at the discovery of the exposed structure as it was thought to be the palace of the first capital city of the Pandya dynasty, an ancient Tamil dynasty of southern India. Two bricks were removed from the structure to determine their ages using the luminescence dating method, and their geochemical composition was analyzed using the X-ray fluorescence method. The bricks were composed of mud that underwent intermediate silicate weathering. High values of anomalous fading rate were observed from both the fine-grain polymineral (9.5–10.5%.decade−1) and coarse-grain K-feldspar (15.5%.decade−1), and this could be attributed to the significant presence of sanidine phase of K-feldspar. The fading corrected luminescence ages (1430–1530 CE) based on the coarse grain K-feldspar of the bricks placed the structure historically in the period of the Vijayanagar Empire, where the Late Pandyas had some autonomy in the south. These age estimates could resolve the hypothesis that the structure was not made by the Early Pandyas (400 BCE−300 CE). This study also reports discrepant ages for coarse quartz grains samples (1,689 CE; ± 10 years, 1 σ) and two fine polymineral grains samples (1634 CE; ± 90 years and 1699 CE; ± 30 years) compared to the age of the coarse K-feldspar grains samples. This discrepancy requires further investigation.